SELF-CLEANING AIR FILTER SYSTEM FOR GAS TURBINE - KAMARUDDIN, MOHD KHAIRUL (UNIVERSITI TEKNOLOGI PETRONAS, 2012)
The project objective is to come out with a new system of self-cleaning air filter system which can operate more efficient compare to the existing self cleaning system. The old self cleaning system is only use the application of timer in boosting of pulse air to clean the filter and this will be a problem as it will shorten the filter lifetime. There is no term of universal filter that can stop all kind of impurities or the air. Application of stage filtration system could be the best way to encounter this problem. This report is about the study of self cleaning air filter system for gas turbine. Self cleaning system is the systems that can self clean the filter at the air intake of the gas turbine while the filter is to dirty. This new system of self cleaning system is operating by using differential pressure transmitter that can measure the dirty level of the filter. The study upon controller tuning method, Programmable logic Controller (PLC), configuration of differential pressure transmitter and the real operation of gas turbine should be done to make sure this project realizable. The author also needs to design the controller by using either using PLC or PID controller. By doing some empirical modelling on process reaction, the author can get the transfer function of the system. The author also needs to choose either PLC is applicable in this project. Some pressure sensor experimental test need to be done to choose the best and efficient sensor that fulfil the criteria to measure the air flow in open area. Site visit had been done at PGB, CUF for the gas turbine real operation. Apart from that, the author also know that the air flow inside the filter house is about 4-5bar. Moreover, from this site visit, the author also gets to know that the system of this self cleaning is a local controller system which means the controller is independent and no access to the control room. The author also takes into consideration to build a small distillation column in this project as it is exist in PGB,CUF self cleaning filter system.